A multiplicidade poética de Emílio Moura: o encanto da hora amarga - Jeronymo, Aline Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The modernist poet Emílio Moura (1902-1971) incorporates a strictly modern language regarding the imagistic suggesting a mainly poetry metalinguistic. That way, from the works Canto da hora amarga (1932) and Cancioneiro (1944) we attest, through the poetic analysis, that modernity Moura’s poetry takes place in confluences with ideas ranging from biblical tradition and come to the depersonalization of the modern I and questing. We objectify, therefore, demonstrate and explore the metalinguistic and intertextual character that results in the personification of poetry, as clarified muse. To achieve this, this same poetry undergoes a dualistic and pessimistic sentiment, baroque, the I that is divided into life and death, light and shadow; goes through a romantic feeling of anguish and desolation and reaches the multiplicity of the poetic speaker, which promotes a constant struggle with the language. More than draw a correlation between classical and modern ideas (in the sense that the poet creates depersonalization and appropriates of free, short prose or verse, typical of modernism), intend to supply, at least in part, the dearth of studies on the miner poet who has found fertile ground to question and analyze internally the role of poetry in the multiplicity of man and modern society to therefore conclude that universalism the Emílio Moura becomes distinctive and mature. Thus, we will check how poetic inflows corroborate both works for reevaluation and critical insertion of poetic the Emílio Moura in the context of modern/Modernist Brazilian literature

O poeta modernista Emílio Moura (1902-1971) incorpora uma linguagem estritamente moderna no que tange à sugestão imagética de uma poesia preponderantemente metalinguística. Dessa forma, é por meio das obras Canto da hora amarga (1936) e Cancioneiro (1945) que buscamos atestar, através de análises poemáticas, que a modernidade emiliana realiza-se em confluências com ideias que vão da tradição bíblica e chegam à despersonalização do eu moderno e questionador. Objetivamos, portanto, comprovar e explorar o caráter metalinguístico e intertextual que resulta na personificação da poesia, aclarada como musa. Para atingir tal intento, essa mesma poesia passa por um sentimento dualista e pessimista, barroco, do eu que se divide em vida e morte, em luz e sombra; passa por um sentimento romântico de angústia e desconsolo e chega à multiplicidade do eu poético, que promove uma constante luta com a linguagem. Mais do que traçar uma correlação entre ideias clássicas e modernas (no sentido em que o poeta cria a despersonalização e apropria-se dos versos livres, curtos ou prosaicos, típicos do modernismo), intencionamos suprir, ao menos em parte, a grande escassez de estudos sobre o poeta mineiro, que encontrou um terreno fértil para questionar e analisar internamente o papel da poesia na multiplicidade do homem e da sociedade moderna para, assim, concluir que o universalismo de Emílio Moura se faz distinto e maduro. Assim sendo, comprovaremos como os influxos poéticos de ambas as obras corroboram para a reavaliação e a inserção crítica da poética de Emílio Moura no contexto da literatura moderna/modernista brasileira
Keywords: Moura, Emilio 1902-1971; Modernismo (Literatura); Poesia brasileira; Brazilian poetry